Figure of the dikpala Agni (the God of fire) - Temples of India Project Team (Jio Institute, 2024)
It is likely a figure of the dikpala Agni (the God of fire) holding a kamandalu (pot) in his left hand. The image of a directional deity that once adorned the temple wall and is now affixed on a late medieval structure on Harsha Hill.